Analiza navzkrižnih subvencij v ekonomskem kontekstu - Ferčič, Aleš (LeXonomica, 2021)
Analysis of cross-subsidies in the economic context. In this article the author analyses the cross-subsidies in an economic context, i.e. he discusses the key methods by which one can assess whether in particular case there exists a cross-subsidy or not. This question is namely of fundamental importance and it must be indispensably answered as a prerequisite for strict legal treatment of the discussed phenomenon. In addition, the author points out that there is no perfect method in this regard and that in practice there are differences in the legal assessment of restrictions of competition performed by undertakings on the one side and by public authorities on the other side. Furthermore, there are differences in their selection within each individual sector. This indicates that the selection of a method of assessment is not a mere technical task, but rather a substantial one, i.e. special measure of current competition or/and liberalization policy. Povzetek. Avtor v prispevku analizira navzkrižne subvencije v ekonomskem kontekstu, tj. obravnava glavne metode, na podlagi katerih se v praksi lahko presoja, ali gre v konkretnem primeru za navzkrižno subvencioniranje, kar je temeljno vprašanje, ki ga je treba rešiti kot predpogoj za striktno pravno obravnavo tega fenomena. Avtor ob tem opozarja, da nobena od obravnavanih metod ni popolna, hkrati pa opozarja tudi na to, da v praksi pri njihovi uporabi prihaja do razlik pri presoji podjetniškega in oblastnega omejevanja konkurence in do razlik pri njihovi uporabi v okviru posameznih sektorjev, kar kaže, da v konkretnem primeru njihova primerna izbira ni golo tehnično opravilo, temveč stvar konkurenčne oz. liberalizacijske politike.